Garner’s Forgotten Novel and Its Relationship to the Stories - Kennedy, Michael P.J. (Studies in Canadian Literature, 1990)
Despite being a novel dismissed by critics as of little interest, Hugh Garner’s Waste No Tears is worthy of examination because of the strong relationship between it and three of Garner’s better known short stories. In the case of "The Yellow Sweater," it appears that the novel borrowed heavily in elements of plot and character from the story. In the case of "Lucy" and "Mama Says to Tell You She’s Out," the stories show a recycling of plot situations and character interactions first developed in Garner’s least known early novel.